Nanostructured materials for photodynamic therapy: synthesis, characterization and in vitro activity - Alea-Reyes, Maria E.; Rodrigues, Mafalda; Serra, Albert; Mora, Margarita; Sagrista, Maria L.; Gonzalez, Asensio; Duran, Sara; Duch, Marta; Plaza, Jose Antonio; Valles, Elisa; Russell, David A.; Pérez-García, Lluïsa (Royal Society of Chemistry, 2017)
Three nanostructured vehicles are proposed as potential carriers for photosensitizers to be used in photodynamic therapy: spherical nanoparticles, hexahedral microparticles and cylindrical magnetic nanorods. A comparative study of their photodynamic properties was performed, and the influence of their size and the amount of loaded porphyrin was considered to discuss their effects in the observed photodynamic activity. All the vehicles have a gold surface, allowing functionalization with a disulphide-containing porphyrin as the photosensitizer, as well as with a PEG-containing thiol to improve their biocompatibility and water solubility. The activity of the porphyrin loaded in each vehicle was assessed through in vitro photocytotoxicity studies using HeLa cells. A synergic effect for the porphyrin toxicity was observed in all of the vehicles. The zinc-containing porphyrin showed better production of singlet oxygen, and proved more photocytotoxic both in solution and loaded in any of the vehicles. The magnetism of the nanorods allows targeting with a magnetic field, but causes their aggregation, hampering the porphyrin's activity. Microparticles showed lower cell internalization but their bigger size allowed a high porphyrin loading, which translated into high photocytotoxicity. The highest cell internalization and photocytotoxicity was observed for the porphyrin-loaded nanoparticles, suggesting that a smaller size is favored in cell uptake.